FGF Family: From Drug Development to Clinical Application - Hui, Qi; Jin, Zi; Li, Xiaokun; Liu, Changxiao; Wang, Xiaojie (International journal of molecular sciences, 2018)
Fibroblast growth factor (FGF) belongs to a large family of growth factors. FGFs use paracrine or endocrine signaling to mediate a myriad of biological and pathophysiological process, including angiogenesis, wound healing, embryonic development, and metabolism regulation. FGF drugs for the treatment of burn and ulcer wounds are now available. The recent discovery of the crucial roles of the endocrine-acting FGF19 subfamily in maintaining homeostasis of bile acid, glucose, and phosphate further extended the activity profile of this family. Here, the applications of recombinant FGFs for the treatment of wounds, diabetes, hypophosphatemia, the development of FGF receptor inhibitors as anti-neoplastic drugs, and the achievements of basic research and applications of FGFs in China are reviewed.